Effects of COVID-19 pandemic on higher education teaching practices in Malaysia / Fatin Aliana Mohd Radzi ... [et al.] - Mohd Radzi, Fatin Aliana; Ainuddin Dahlan, Nadia; Wan Yunus, Farhana; Malik, Melissa; Said Hashim, Khadijah (Universiti Teknologi MARA, 2024)
This paper presents an initial investigation into the transformations observed in the learning processes within Malaysian educational institutions following the onset of the COVID-19 pandemic. Like educational systems worldwide, Malaysia has undergone significant adjustments in response to the spread of the virus. The study specifically examines the characteristics and challenges faced by Malaysian universities as they transition to online and blended learning during this era of global isolation. Utilizing a set of questionnaires, the research explores the pandemic's impact on teaching practices in Malaysia across content, instructional delivery, and assessment. Findings suggested that the COVID-19 pandemic has posed significant challenges to the global education system, compelling institutions and educators to adapt quickly to online teaching. While adjustments were made in course content, the shift leaned towards more theoretical aspects, raising questions about the efficacy of this approach for student learning. Despite shortcomings, educators managed to achieve course learning outcomes. This study aims to provide insights into adaptive strategies for the new norms of teaching and learning, ensuring the continuity of education for all amid changing circumstances and crises.